PATIENT WITH PRIMARY PULMONARY HYPERTENSION – WHO HE IS AND HOW TO HELP HIM? - S. V. Garkina (Klinicist, 2014)
Differential diagnostic search in patients with pulmonary hypertension is always difficult clinical problem. This article describes the clinical case of treating patient with high risk primary pulmonary hypertension.